2019
DOI: 10.1001/jamanetworkopen.2019.4223
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Professional American-Style Football Players and Professional American Baseball Players

Abstract: Key Points Question What are the long-term health risks of National Football League (NFL) players compared with Major League Baseball (MLB) players, another group of elite athletes? Findings In this cohort study of 3419 NFL and 2708 MLB players, NFL players had significantly higher mortality rates from all causes, cardiovascular diseases, and neurodegenerative diseases compared with MLB players. Meaning This study found that NFL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(122 citation statements)
references
References 50 publications
8
113
0
1
Order By: Relevance
“…Finally, evidence from the external comparison groups provide grounds for assessing the overall effect of sport participation, including all pros and cons, and it is expected to be associated with better health due to a selection effect, and also partially to the physical activity, and general healthy habits that athletes display in comparison with any non-athlete group (healthy cohort effect), as previously found 43 44. Nonetheless, this selection effect might be heterogeneous across sports,45 and it might be mitigated by the emergence of some lifestyle choices after retirement, as demonstrated for increased body mass index 48. However, overall, an inverse associations between participating in sports and general health (specifically for cardiovascular diseases and cancer outcomes) is expected, including the overall risk of dementia when athletes are compared with the general population.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, evidence from the external comparison groups provide grounds for assessing the overall effect of sport participation, including all pros and cons, and it is expected to be associated with better health due to a selection effect, and also partially to the physical activity, and general healthy habits that athletes display in comparison with any non-athlete group (healthy cohort effect), as previously found 43 44. Nonetheless, this selection effect might be heterogeneous across sports,45 and it might be mitigated by the emergence of some lifestyle choices after retirement, as demonstrated for increased body mass index 48. However, overall, an inverse associations between participating in sports and general health (specifically for cardiovascular diseases and cancer outcomes) is expected, including the overall risk of dementia when athletes are compared with the general population.…”
Section: Discussionmentioning
confidence: 88%
“…However, these differences are very unlikely to be exclusively due to concussion, they could be confounded by any other characteristics of the athletes included (eg, use of licit/illicit drugs, alcohol intake, lifestyle and psychosocial risk factors, etc). Moreover, one would expect to see among the former athletes a healthy cohort effect with decreased prevalence of cardiovascular disease and cancer risk factors,43 44 although to what extent this is consistent across generations and across sport disciplines, is to date unclear 45. On the other hand, studies investigating cognitive functions with neuropsychological batteries, in most cases find subtle, although statistically significant, differences which are not easy to interpret in terms of clinical significance 28 29 31 33 42.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests EPA and DHA may reduce cardiovascular risk factors such as dyslipidemia and high blood pressure [58][59][60] and even sudden death related to cardiac causes [61][62][63][64][65], which are applicable to a wide variety of athletes. This will continue to be of particular interest for higher mass athletes (such as linemen in American football) observed to be at higher risk of cardiovascular disease and metabolic syndrome [61,66,67]. Given this concern, in combination with the associated health functions of ω-3 FA related to both athlete performance and well-being [2, 3, 8-13, 15-24, 26], a focus on improved O3i is warranted.…”
Section: Plos Onementioning
confidence: 99%
“…While society considers intervening, we urge continued research, especially in the following areas: (1) looking for natural experiments such as the studies of improved lung function and reduced mortality during short-duration improvements in air quality during Olympic Games and the like, 64 where we might see rapid changes in some marker of outcome during perturbations in exposure; (2) mounting epidemiological studies where the unexposed group comprises athletes without RHI exposure, thereby minimizing the healthy worker effect i (refer to as this article was in press, Nguyen et al 65 reported on just such a study: they compared 3415 former NFL players born between 1915 and 1965 with 2708 former Major League Baseball (MLB) players born in the same time period. They documented a statistically-significant three-fold ratio (NFL:MLB) of neurodegenerative diseases as the underlying or contributing cause of death across the two athlete groups); (3) trying to develop the most biologically meaningful indices of peak and of cumulative exposure to forces that cause CTE; and (4) further validating the supposition that CTE is rare in subpopulations without RHI.…”
Section: From Analysis To Actionmentioning
confidence: 99%